2022
DOI: 10.1177/15353702221108925
|View full text |Cite
|
Sign up to set email alerts
|

Green tea epigallocatechin gallate suppresses 3T3-L1 cell growth via microRNA-143/MAPK7 pathways

Abstract: Green tea epigallocatechin gallate (EGCG) and microRNA (miRNA) molecules modulate obesity. Nevertheless, it is still unknown whether EGCG modulates fat cell growth via miRNA-related signaling. In this study, white preadipocytes were used to examine whether the antimitogenic effect of EGCG on fat cells is regulated by the miR-143/MAPK7 pathway. We showed that EGCG upregulated the levels of miR-143, but not miR-155, in 3T3-L1 preadipocytes. Moreover, EGCG downregulated MAPK7 mRNA and protein levels time- and dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…The combined treatment of catechin epigallocatechin gallate (EGCG) and quercetin prevented insulin resistance by increasing the expression of miR-27a-3p and miR-96-5p, which directly target Forkhead Box O1 (FOXO1), reducing the production of glucose and the transcription of gluconeogenic enzymes [ 97 ]. In addition, ECGC showed therapeutic potential in obesity inhibiting white and beige 3T3-L1 and D12 preadipocyte growth by upregulated miR-let-7a and subsequent high-mobility group AT-hook 2 (HMGA2) suppression [ 98 ] and inhibiting the MAPK7 pathway by increased miR-143 levels [ 99 ]. Clinical data from a cohort of women affected by overweight and insulin resistance revealed that blood orange juice consumption (500 mL per day) for four weeks resulted in upregulated miR-144-3p, miR-424-5p, miR-144-3p, and miR-130b-3p and decreased let-7f-5p and miR-126-3p levels in peripheral blood mononuclear cells, leading to attenuated IL-6 and NF-κB mRNA expression [ 100 ].…”
Section: Food-derived Nutrients As Mirna Regulators In Chronic Diseasesmentioning
confidence: 99%
“…The combined treatment of catechin epigallocatechin gallate (EGCG) and quercetin prevented insulin resistance by increasing the expression of miR-27a-3p and miR-96-5p, which directly target Forkhead Box O1 (FOXO1), reducing the production of glucose and the transcription of gluconeogenic enzymes [ 97 ]. In addition, ECGC showed therapeutic potential in obesity inhibiting white and beige 3T3-L1 and D12 preadipocyte growth by upregulated miR-let-7a and subsequent high-mobility group AT-hook 2 (HMGA2) suppression [ 98 ] and inhibiting the MAPK7 pathway by increased miR-143 levels [ 99 ]. Clinical data from a cohort of women affected by overweight and insulin resistance revealed that blood orange juice consumption (500 mL per day) for four weeks resulted in upregulated miR-144-3p, miR-424-5p, miR-144-3p, and miR-130b-3p and decreased let-7f-5p and miR-126-3p levels in peripheral blood mononuclear cells, leading to attenuated IL-6 and NF-κB mRNA expression [ 100 ].…”
Section: Food-derived Nutrients As Mirna Regulators In Chronic Diseasesmentioning
confidence: 99%
“…A detailed investigation of ferroptosis responses for these natural products and miRNAs is warranted. Curcumin [272] miR-125b-5p PEITC [273], quercetin [274], EGCG [275], berberine [276] miR-1287-5p Curcumin [277] miR-129-5p Matrine [278] miR-142-3p Artesunate [279], quercetin [280], curcumin [281] miR-143-3p Curcumin [282], EGCG [283,284], sulforaphane [285], quercetin [286] miR-144-3p Curcumin [287] miR-15a-5p Curcumin [288], baicalin [289], Withaferin A [290] miR-15a-3p EGCG [284] miR-205-5p Cryptotanshinone ↓ [291] proanthocyanidins ↓ [292], curcumin [293] miR-214-3p EGCG [284], sulforaphane [285] miR-25-3p Withaferin A [294] miR-27a-3p β-elemene [295], quercetin [296] miR-28-5p Curcumin [297] miR-302a-3p Curcumin [298] miR-324-3p Salinomycin ↓ [299] miR-365a-3p Sulforaphane [300] miR-375-3p Solasonine [301] miR-409-3p Curcumin [302] miR-429 Curcumin [303], berberine ↓ [304,305] miR-489-3p Curcumin [306] Ferroptosisinhibiting miRNAs miR-18a-5p Curcumin ↓ [307] miR-19a-3p Berberine [308], proanthocyanidins …”
Section: Ferroptosis-modulating Mirnas Are Associated With Some Natur...mentioning
confidence: 99%
“…Curcumin inhibits autophagy and enhances the radiosensitivity of prostate cancer cells by upregulating miR-143-3p [ 282 ]. EGCG inhibits the proliferation of preadipocytes [ 283 ] and breast cancer cells [ 284 ] by upregulating miR-143-3p. Additionally, gastric cancer cells express low levels of miR-143-3p.…”
Section: Ferroptosis-modulating Mirnas Are Associated With Some Natur...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, there remains deficiencies in both cell and animal research methodologies. Cell research normally focuses on one or several cellular components [5,6] and, thus, cannot well describe biological processes occurring in vivo. Despite animal research being able to reproduce various disease processes [7,8], issues such as long experimental periods [9], animal mortality [10], ethics [11], and economics [12] remain problematic.…”
Section: Introductionmentioning
confidence: 99%